2018
DOI: 10.1002/star.201800060
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Physicochemical Properties of Resistant Starch Prepared by Autoclaving‐Microwave

Abstract: This work is focused on evaluating the structure (granular morphology, crystalline structure, molecular order structure), and properties (resistant starch content, swelling power, amylose leaching) of resistant starch (RS) prepared from corn starch by an autoclaving and autoclaving-microwave method. The results indicated that compared with native starch, all of the RS granules became loose, bigger, and rough fragmented, and displayed a B þ V crystalline structure. Meanwhile, the relative crystallinity, helix c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 35 publications
0
10
1
Order By: Relevance
“…This phenomenon is affected by amylopectin branch length as well. Longer amylopectin branch resulted in more packed double helices structure ( 66 ). It was also observed in annealing modification ( 67 ).…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon is affected by amylopectin branch length as well. Longer amylopectin branch resulted in more packed double helices structure ( 66 ). It was also observed in annealing modification ( 67 ).…”
Section: Resultsmentioning
confidence: 99%
“…While being stored for 24 h, the cooked starches showed irregular shapes with a compact and smooth surface [ 27 , 45 ], similar to that of starches with high temperature–pressure [ 46 ] or microwave treatment [ 47 ]. Research has consistently reported that autoclaved microwave-treated starches show irregular shapes after storage for 24 h, and the size of starch aggregates exceeded 100 μm [ 48 ]. That is, the glucan chains of starch undergo reassembly during storage and increase the bulk density of starch matrices.…”
Section: Resultsmentioning
confidence: 99%
“…It is also nutritionally very important since it supplies the major portion of the carbohydrates in the diet (Li et al, 2018). Keeling and Myers stated (2010) that more than 80 percent of the calories in the world arouse from starch which was a unique supplement in our nutrition.…”
Section: Starchmentioning
confidence: 99%